Betawi Cultural Village, The Last Asylum - Hendrico Firzandy (ULTIMART Jurnal Komunikasi Visual, 2017)
SB Betawi Cultural Village is a region defined by the Jakarta administration as cultural preservation area. This research will discuss the link between this village with politics, history of Betawi ethnic origin, as well as field visits. This research will conduct a view from two perspectives, one is the perspective of an architect and the other is of a commoner. This research tries to understand the meaning of the presence of this cultural village and how it was presented as a preservation and reservation area, not only the nature but also the Betawi culture and ethnic. In addition, this research also describes an understanding of the participation of politic, architecture and space in building the image of the region and at the same time creating a development boundary. Because of the sensitive topic of this research then the subject has to be abbreviated into ‘SB’. Keywords: Betawi people, cultural village, heritage, power